WORKPLACE STRESS AMONG EMPLOYEES: CAUSES, CONSEQUENCES, AND EFFECTIVE MANAGEMENT STRATEGIES - Pandey, Krishna Chandra; Mushtaq, Shahnawaz (International Journal of Research -GRANTHAALAYAH, 2024)
Stress at workplace has turned out to be a major problem that has impacted employee well being and performance at work place. The paper discusses the key causes, effects, and ways of managing stress in the workplace among the workers. The quantitative research methodology was employed through a structured questionnaire that was administered to 100 employees involved in the private and the public sector. The results show that work overload, job insecurity and extended working hours are the major causes of stress at work. The research also states that stress in the work place would have a number of adverse effects that include; reduced productivity, health issues and dissatisfaction with the job. Some of the coping mechanisms embraced by employees to deal with stress are time management, bodily workouts as well as meditation. The research points out the importance of good organizational policies and good working conditions to curb stress and enhance the well-being and productivity of the employees.